2020
DOI: 10.1016/j.hrthm.2020.05.014
|View full text |Cite
|
Sign up to set email alerts
|

QT interval prolongation and torsade de pointes in patients with COVID-19 treated with hydroxychloroquine/azithromycin

Abstract: BACKGROUND There is no known effective therapy for patients with coronavirus disease 2019 . Initial reports suggesting the potential benefit of hydroxychloroquine/azithromycin (HY/ AZ) have resulted in massive adoption of this combination worldwide. However, while the true efficacy of this regimen is unknown, initial reports have raised concerns about the potential risk of QT interval prolongation and induction of torsade de pointes (TdP).OBJECTIVE The purpose of this study was to assess the change in correcte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
266
4
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(292 citation statements)
references
References 32 publications
(39 reference statements)
12
266
4
10
Order By: Relevance
“…Unfortunately, on the clinical aspect, LPV/r failed to demonstrate clinical benefits in well-powered randomized controlled trials (RCTs), while HCQ and/or AZ also failed to demonstrate benefits in observational studies (12)(13)(14). Meanwhile, LPV/r, CQ/HCQ and AZ may even increase the incidence of adverse events (14)(15)(16). Although remdesivir is widely considered one of the most promising candidates, latest RCTs only revealed marginal shortening of disease duration in patients treated (17).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, on the clinical aspect, LPV/r failed to demonstrate clinical benefits in well-powered randomized controlled trials (RCTs), while HCQ and/or AZ also failed to demonstrate benefits in observational studies (12)(13)(14). Meanwhile, LPV/r, CQ/HCQ and AZ may even increase the incidence of adverse events (14)(15)(16). Although remdesivir is widely considered one of the most promising candidates, latest RCTs only revealed marginal shortening of disease duration in patients treated (17).…”
Section: Introductionmentioning
confidence: 99%
“…One case of torsades de pointes (TdP) which happened three days after discontinuation of treatment may indicate delayed risk possibly due to long half-life of HCQ (11). A larger retrospective cohort study of 251 subjects showed prolongation of QTc≥500 ms in 15.9 % of subjects with 1 case of TdP (12). The timing of peak ΔQTc of this study was at the end of the 5-day treatment scheme.…”
Section: Discussionmentioning
confidence: 61%
“…Despite the fact that HCQ/CQ were commonly used for rheumatoid arthritis and systemic lupus erythematosus in the general population, there has been major concern with widespread use of these medications for COVID-19 due to possible QTc prolongation and induction of life-threatening arrhythmias. There is general consensus that QTc prolongation after HCQ/CQ use may occur in a dose-dependent way [11,[32][33][34][35]. Previous studies demonstrated that HCQ/CQ block the hERG potassium channels, extending ventricular repolarization and action potentials, and hence, may trigger ventricular tachyarrhythmias [36,37].…”
Section: Discussionmentioning
confidence: 99%